Identifikasi Kendala Relawan Demokrasi Basis Perempuan sebagai Fasilitator Pendidikan Pemilih di Kota Pekanbaru dan Kota Dumai - Hariyanti, Hariyanti; Hambali, Hambali (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This study aims to describe the obstacles faced by Democracy Volunteers, a social movement partnering the General Election Commission (KPU) in improving voters’ education in the 2019 simultaneous regional election in the cities of Pekanbaru and Dumai, Riau province. Democracy Volunteer has the principle “from voters to voters”, because as facilitators, they come from the community that they will educate. This research used a qualitative approach with descriptive method. Informants were determined through non-probability sampling technique using purposive sampling technique. The number of research informants amounted to nine people consisting of the KPU commissioners and staff in charge of the Democracy Volunteer program, as well as Democracy Volunteers members for women voters. The data validity was tested using triangulation of data sources. The findings of the study show that in carrying out its duties as the facilitators of voter education, the Democracy Volunteers experience several obstacles, including (1) limited working time for volunteers; the allocated two-month time meant that not all regions could be visited to spread information on election and democracy; (2) limited time for the implementation of voter education activities in the community; (3) limited knowledge of Democracy Volunteers regarding electoral technicality and the lack of confidence in delivering material to the community so that only certain internal volunteers are relied on while others are only tasked with facilitating activities such as distributing snacks, installing banners and preparing attendance; (4) the apathy of the target community towards electoral information hence it is quite difficult to provide understanding and even motivation to participate in the election. Democracy Volunteers are partners of the KPU in inviting the public to become smart and responsible voters in order to accomplish quality elections. Keywords: Democracy Volunteer, women voters, voter education ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan kendala yang dihadapi Relawan Demokrasi, mitra Komisi Pemilihan Umum dalam meningkatkan pengetahuan pemilih dalam pemilu, pada pemilu serentak 2019 di Kota Pekanbaru dan Kota Dumai, terutama basis pemilih perempuan. Relawan Demokrasi mempunyai konsep “dari pemilih kepada pemilih”, sebab sebagai fasilitator, mereka berasal dari komunitas yang akan diedukasinya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Penentuan informan penelitian melalui teknik non-probability sampling dengan teknik purposive sampling. Informan penelitian berjumlah sembilan orang yang terdiri dari komisioner, staf KPU yang mengurusi program Relawan Demokrasi, dan Relawan Demokrasi basis perempuan. Teknik pengujian keabsahan data menggunakan triangulasi sumber data. Temuan penelitian menunjukkan bahwa dalam melaksanakan tugasnya sebagai fasilitator pendidikan pemilih, Relawan Demokrasi mengalami beberapa kendala di antaranya (1) keterbatasan waktu masa kerja Relawan Demokrasi; waktu yang diberikan selama kurang lebih dua bulan menyebabkan tidak semua daerah bisa dikunjungi dalam memberikan informasi kepemiluan dan demokrasi; (2) keterbatasan waktu pelaksanaan kegiatan pendidikan pemilih dalam komunitas; (3) keterbatasan pengetahuan Relawan Demokrasi mengenai teknis kepemiluan serta minimnya kepercayaan diri dalam menyampaikan materi kepada komunitas sehingga narasumber dari internal relawan hanya orang tertentu yang diandalkan sementara yang lainnya hanya bertugas memfasilitasi kegiatan seperti pembagian camilan, pemasangan spanduk/banner dan mempersiapkan presensi; (4) apatisme komunitas sasaran terhadap informasi kepemiluan sehingga cukup menyulitkan dalam memberikan pemahaman bahkan motivasi untuk ikut berpartisipasi dalam pemilu. Relawan Demokrasi sebagai partner KPU mengajak masyarakat untuk menjadi pemilih cerdas dan bertanggung jawab guna mewujudkan pemilu yang berkualitas.